Striae Gravidarum, Acne, Facial Spots, and Hair Disorders: Risk Factors in a Study with 1284 Puerperal Patients - Isadora da Rosa Hoefel; Magda Blessmann Weber; Ana Paula Dornelles Manzoni; Bárbara Hartung Lovato; Renan Rangel Bonamigo (Hindawi Limited, 2020)
Objective. To determine the prevalence of skin changes during pregnancy and to relate their occurrence to specific factors in a population of south Brazil. Methods. A cross-sectional analytical study was carried out with 1284 puerperal patients. A questionnaire about skin changes during pregnancy was developed and applied by the authors to all puerperal women admitted in a tertiary hospital in south Brazil. Results. The appearance of striae during pregnancy was reported by 633 women (49.5%) and had a statistically significant association with primiparity, presence of stretch marks before pregnancy, and gestational weight gain above 21 kg. Facial blemishes were reported by 33.9% (n=434) and were associated with a positive family history, multiparity, and the use of facial sunscreen (p<0.0001). The onset or worsening of acne was identified in 35.7% (n=456) and was statistically associated with primiparity and Fitzpatrick phototypes IV and V. Hair alterations were reported by 44.5% (n=569) and were associated with primiparity (p=0.029). Conclusion. Although most of the skin changes during pregnancy are considered "physiologic," they can cause significant discomfort. Thus, it is important to know them and to understand which risk factors may be associated with such changes.